Analysis applicability of 360-degree feedback performance appraisal as a new technique performance appraisal for civil servants - Toman Sony Tambunan; Paham Ginting; Sirojuzilam Sirojuzilam; Yeni Absah (Universitas Pendidikan Nasional, 2021)
The literature on 360-degree feedback performance appraisal systems has attracted considerable attention by showing a link between behavior change and individual performance. This study aimed to analyze the strengths, weaknesses, opportunities, and threats to the 360-degree feedback performance appraisal system for Civil Servants in the City Government of Medan. To determine the participants in this study, it was calculated using the formula, Slovin. The data was collected through observations, interviews, and literature studies. Data analysis used qualitative descriptive analysis. The data results would be used to determine the strengths, weaknesses, opportunities, and threats to the implementation of the Civil Servants' 360-degree feedback performance assessment system in the City Government of Medan. The strategy of implementing a 360-degree feedback performance appraisal system as a performance assessment system for Civil Servants in the City Government of Medan was creating a joint commitment to support a fair and objective performance appraisal system, implement a 360-degree feedback performance appraisal system as an effective performance appraisal system for Civil Servants in the City Government of Medan, involving the participation of many parties to formulate assessment instruments, involving the participation of several parties at each interconnected level to act as an assessment team, improving the competence of human resources in conducting the appraisal process, establishing performance appraisal instruments that reflect aspects of actual attitudes, behaviors, morals, skills, and work outcomes, creating stages and performance appraisal standards, and using information and communication technology (ICT) in the delivery of appraisal instruments.